Exploring the Role of Arabic in Developing Social Behavioral Character - Muliara, M.A.Qoyyum; Jinan, Ulfi Samaratul; Syafira, Luthfiati (Jurnal Al-Maqoyis, 2025)
Arabic does not only function as a means of communication or a means of understanding Islamic texts, but also has an important contribution in character formation, especially social behavior. The Arabic language learning process integrates a holistic approach that includes cognitive (knowledge), affective (attitude), and psychomotor (skills) aspects. This approach allows students not only to understand Arabic intellectually, but also to be able to form a personality with a strong and noble character. The purpose of the study was to explore the role of Arabic in developing the character of students' social behavior. The study used a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews and documents. The research objects consisted of nine people including managers, administrators, and students at the Markaz Arabiyah Arabic language course institution, Pare Kediri. The results of the study showed that Arabic language learning has explored the role of the development of students' social character. Which includes (1) Trustworthiness in worship, trustworthiness in guarding property, and trustworthiness in work; (2) Honesty in speaking, honesty in keeping promises, and honesty in acting; (3) Justice in the family, justice in work, and justice in the aspect of education. For it, can be concluded that learning Arabic not only improves language competence from an intellectual perspective, but also strengthens the social character needed in community life.